THE EFFECT YOGA GYMNASTIC TO BLOOD PRESSURE FLUCTUATION ON HYPERTENSION PATIENTS AT SUMOCALI VILLAGE SCANDI DISTRICT SIDOARJO REGENCY - muhammad sajidin; RARAS MERBAWANI; ASEF WILDAN MUNFADLILA (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2017)
Background: Hypertension is the most common disease found in the community, not only lowers quality of life, but can be life-threatening. Hypertension is known as heterogeneous group of disease because it can affect anyone from different age groups and various economic classes. One of the non-pharmacological therapy for hypertension is yoga exercises. Research Objectives: To determine the effect of yoga exercises on blood pressure in hypertensive patients in Sumokali village, Candi district, Sidoarjo regency. Research Method: This research method using one group pre test - post test design. The sampling technique used simple random sampling, with population of hypertension patients in Sumokali Village, Candi District of Sidoarjo Regency and a large sample of 18 people according to criteria. Data collection used interval scale and instrument used is observation sheet. This yoga exercise was done for 2 weeks in the morning or afternoon. Result: The result of Paired T-Test test shows that the value of Ï-Value (0,000) <Î± (0,05) as well as the result that yoga gymnastics have an effect on fluctuation of blood pressure in hypertension patient in Sumokali Village, Candi District of Sidoarjo Regency. Conclusion: Gymnastics yoga was one effective therapy, easy to do and useful. Because yoga gymnastics can make the body become relaxed and blood vessels become vasodilates so that the blood flow and oxygen supply become smooth. Keywords: yoga gymnastics, blood pressure, hypertension patient.